2016
DOI: 10.1007/s11695-016-2439-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Bariatric Surgery in the Public Healthcare System in Brazil: Real-World Evidence from a High-Volume Obesity Surgery Center

Abstract: BackgroundThis study aimed to evaluate the waiting time, safety, and effectiveness of bariatric surgery based on real-world data.MethodsThis is a noninterventional, noncomparative, and retrospective study with 300 morbidly obese patients who had undergone open Roux-en-Y surgery.ResultsThe procedure was found to be very safe, with low rates of overall complications (10.7%). Approximately 48.4% of the patients had reached a BMI <30 mg/kg2 at 12 months after surgery, while 6% were still classified as morbidly obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
0
8
0
2
Order By: Relevance
“…BS appears to be an effective tool for the treatment of obesity and for obesity-related comorbidities, including SAH, DM, dyslipidemia, and cardiovascular events, as well as a means to reduce mortality [6,7,8]. Conservative treatment, diet, and exercise have been established to induce significant weight loss and increase aerobic fitness along with a cardiometabolic benefit [7].…”
Section: Introductionmentioning
confidence: 99%
“…BS appears to be an effective tool for the treatment of obesity and for obesity-related comorbidities, including SAH, DM, dyslipidemia, and cardiovascular events, as well as a means to reduce mortality [6,7,8]. Conservative treatment, diet, and exercise have been established to induce significant weight loss and increase aerobic fitness along with a cardiometabolic benefit [7].…”
Section: Introductionmentioning
confidence: 99%
“…These diseases contribute to both significant deterioration of health condition and premature death [7]. Studies performed in a population of 900 thousand adults demonstrated that obesity reduces life expectancy by 2 to 4 years, whereas morbid obesity reduces it by up to 10 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…Morbid obesity is frequently associated with concomitant diseases, including hypertension, diabetes, coronary arterial disease, cholecystic diseases, hepatic fibrosis and fatty degeneration of the liver, dyslipidaemia, osteoarthritis and certain neoplasms. These diseases contribute to both significant deterioration of health condition and premature death [ 7 ]. Studies performed in a population of 900 thousand adults demonstrated that obesity reduces life expectancy by 2 to 4 years, whereas morbid obesity reduces it by up to 10 years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of severe obesity, bariatric surgery has been the best alternative treatment. Brazil's Sistema Único de Saúde (SUS, Brazilian Unified Health System) provides this surgical procedure, but the number of surgeries performed is still insufficient [4,5], resulting in a long waiting period, which can last from three to seven years [5,6]. The reduction of 5 to 10% of body weight before bariatric surgery decreases the surgical complications and comorbidities associated with obesity, and in some cases may prevent surgery through the adoption of new habits [4,7,8].…”
Section: Introductionmentioning
confidence: 99%